Trending Racial and Socioeconomic Inequality in the Surgical Management and Outcome of Traumatic Cervical Spinal Cord Injury With Fracture In the USA From 1998 to 2009. (1st September 2019) - Dru, Alexander; Neal, Dan; Fox, W Christopher; Hoh, Brian Lim; Hoh, Daniel J
Abstract: INTRODUCTION: Advances in treatment of traumatic cervical spinal cord injury with fracture (TCSCIF) have led to significant improvements in clinical outcomes; however, progress in healthcare is seldom ubiquitous across demographic groups. We explored if disparities in treatment and outcome after TCSCIF exist across race and socioeconomic status. METHODS: We queried the Nationwide Inpatient Sample database from 1998 to 2009 for TCSCIF hospitalizations. Multivariate analysis was used to identify the correlation between socioeconomic status and race to treatment type and outcome. RESULTS: There were 21 985 admissions for TCSCIF. In all 66.9% had a favorable discharge disposition. In-hospital mortality rate was 12.5%. In all 43.7% underwent surgery. Overall, surgery was associated with lower in-hospital mortality (OR 0.30, 95% CI 0.27-0.34, P < .01) and better discharge disposition (OR 0.68, 95% CI 0.62-0.74, P < .01) vs nonsurgical or no intervention. Controlling for race and socioeconomic status demonstrated higher status (HS) non-Caucasians had lower odds of receiving surgery than HS Caucasians (OR 0.89, 95% CI 0.81-0.97, P = .01). LSES non-Caucasians had lower odds of receiving surgery than HS Caucasians (OR 0.83, 95% CI 0.73-0.94, P < .01). HS non-Caucasians had lower odds of receiving surgery than LSES Caucasians (OR 0.87, 95% CI 0.77-0.99, P = .03). LSES non-Caucasians had lower odds of receiving surgery than LSES Caucasians (OR 0.82, 95% CI 0.71-0.94, P = .01). For favorable discharge status HS non-Caucasians, LSES non-Caucasians, and LSES Caucasians all had lower odds of favorable discharge compared to HS Caucasians (OR 0.83, 95% CI 0.73-0.95, P = .01/OR 0.69, 95% CI 0.59-0.81, P < .01/OR 0.75, 95% CI 0.66-0.85, P < .01), respectively. CONCLUSION: In our multivariate model that controlled for race and socioeconomic status in the setting of TCSCIF, race (but not socioeconomic status) was a factor in receiving surgery and both race and LSES impacted favorable discharge.